Comparative study of physicochemical, nutritional, phytochemical, and sensory properties of bread with plantain and soy flours partly replacing wheat flour - Udomkun, Patchimaporn; Masso, C.; Swennen, Rony L.; Romuli, S.; Innawong, B.; Fotso Kuate, A.; Akin-Idowu, P.E.; Alakonya, A.; Vanlauwe, Bernard (Wiley, 2022)
Plantain flour (PLF) and soy flour (SF) were used to substitute wheat flour (10% and 20% w/w) in composite bread. Physicochemical, phytochemical, and sensory properties were investigated. Partial substitution by PLF significantly increased (p < .05) starch, amylose, ascorbic acid, and potassium content in bread samples. In contrast, a significant improvement (p < .05) in protein, fat, amylopectin, and calcium content was observed with SF substitution. Composite bread with PLF and SF together lowered the hydrolysis index (HI) and glycemic index (GI) as compared with whole wheat flour. The molar phytate to minerals (iron, zinc, and calcium) ratio in all composite loaves was lower than reported critical values, except for phytate to iron. Significant differences (p < .05) were found in color, specific volume, and texture characteristics of loaves made from partial substitution with PLF and SF. Sensory evaluation revealed that bread with 10% PLF exhibited better scores for appearance and willingness to pay than the control. In contrast, SF negatively affected (p < .05) the appearance, texture, color, overall acceptance, and willingness to pay. The trade-off analysis indicated that PLF can be utilized to produce bread that meets consumers' demands, while incorporating SF as an alternative high-nutrient density bread will be beneficial to health.